Mathematical model to support pathological assessment and its integration into a web tool - Rafael Otal; Pedro Enrique Pérez (Anales de Edificación)
This mathematical model evaluates various quality requirements such as safety, habitability, functionality and even aesthetics. In its development, it was intended to be understandable for the greatest number of users. This translates into a simple weighting that can be expressed as follows: GP = E + H + F + So + Se Its use is very simple, the technician who assesses the damage of a building often has to fill in some fields to categorise and analyse his data. These fields are represented in a form where each piece of information has a numerical value. This form, in turn, is integrated into a web tool so that numerical values are automatically obtained as the information is entered. Throughout this article, the operation of this mathematical model will be developed, the variables taken into account will be explained and it will be shown how it can support decision-making